2021
DOI: 10.2174/1389203722666210325110231
|View full text |Cite
|
Sign up to set email alerts
|

Synaptotagmin-1: A Multi-Functional Protein that Mediates Vesicle Docking, Priming, and Fusion

Abstract: : The fusion of secretory vesicles with the plasma membrane depends on the assembly of v-SNAREs (VAMP2/synaptobrevin2) and t-SNAREs (SNAP25/syntaxin1) into the SNARE complex. Vesicles go through several upstream steps, referred to as docking and priming, to gain fusion competence. The vesicular protein synaptotagmin-1 (Syt-1) is the principal Ca2+ sensor for fusion in several central nervous system neurons and neuroendocrine cells and part of the docking complex for secretory granules. Syt-1 binds to the accep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The syp is a marker protein of synaptic vesicles and is altered by synaptic dysfunction [ 46 ]. Syt-1 is a multifunctional protein producing vesicle docking, excitation, and fusion [ 47 ]. The results of immunoblotting showed that the expression of PSD95, syt-1, and syp was greatly increased in the NTG + VEH group compared with that in the saline + VEH group, while repeated treatment with PACAP6-38 markedly reduced the expression of these three proteins in the NTG + PA6-38 group ( p < 0.001; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The syp is a marker protein of synaptic vesicles and is altered by synaptic dysfunction [ 46 ]. Syt-1 is a multifunctional protein producing vesicle docking, excitation, and fusion [ 47 ]. The results of immunoblotting showed that the expression of PSD95, syt-1, and syp was greatly increased in the NTG + VEH group compared with that in the saline + VEH group, while repeated treatment with PACAP6-38 markedly reduced the expression of these three proteins in the NTG + PA6-38 group ( p < 0.001; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since Syt1 facilitates secretory vesicles docking to and fusion with plasma membrane through interaction with SNARE complex [ 25 ], we next examined whether Rab26 influences the interaction between Syt1 and SNARE complex. 293t cells were cotransfected with myc-Rab26 and GFP-SNAP25 or GFP-Syntaxin-1; the cell lysates were subjected for GST-pulldown using GST-Syt1.…”
Section: Resultsmentioning
confidence: 99%
“…J is the quantitative data from K. The images were performed with 4 mice pancreas in each of the 2 groups. (L) Western blot showed that Rab26 protein expression increased after 25…”
Section: Rab26 Interacts With Synaptotagmin-1mentioning
confidence: 99%
“…The most important role of C2 domains is to activate membrane-associated protein modules in a Ca 2+dependent manner. Therefore, from this group, we selected GRMZM2G442551/Zm00001d046508, a putative phospholipase D alpha (annotated as phospholipase Dα5 in maize) with three C2 domains, GRMZM2G100864/Zm00001d036801, a predicted Ca 2+ -dependent lipid-binding phosphoribosyltransferase family protein with two C2 domains and whose putative Arabidopsis homologs, FTIP3 and 4 (FT INTERACTING PROOTEIN 3 and 4), are required for intracellular protein trafficking in meristematic tissues (Liu et al, 2018), and GRMZM2G050193/Zm00001d006238, which is a synaptotagmin-like protein and therefore potentially able to bind phospholipids, induce membrane curvature, and mediate contact sites between organelles (Ullah et al, 2021).…”
Section: Candidate Proteins With Potential Function(s) In Maize Aleur...mentioning
confidence: 99%